2014
DOI: 10.2478/eko-2014-0006
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of modern and traditional methods of soilsorption complex measurement : the basis of long -term studies and modelling

Abstract: This paper presents the correlations between two different analytical methods of assessing soil nutrient contents. Soil nutrient content measurements measured using the flame atomic absorption spectrometry (FAAS ) method, which uses barium chloride extraction, were compared with those of the now-unused Gedroiz method, which uses ammonium chloride extraction (calcium by titration, magnesium, potassium and sodium by weighing). Natural forest soils from the Ukrainian Carpathians at the localities of Javorník and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Soil changes over a 40-year horizon were addressed in four different soil taxonomical units by Hédl and Rejšek [75] at the soil texture, soil reaction, carbonates and organic carbon content levels. In addition to the incompatibility of laboratory methods, which represent a problem in pedological long-term studies [76,77], the authors concluded that the temporal changes were insignificant, and neither the leaching of carbonates nor decreases in soil reaction joined with acidification or soil environment impoverishment occurred due to nutrient depletions. Alterations in soil properties on a physicochemical basis can be expected with an uncertain trend due to the buffering capacity [78].…”
Section: Temporal Aspect Of Changes In Soil Environmentmentioning
confidence: 99%
“…Soil changes over a 40-year horizon were addressed in four different soil taxonomical units by Hédl and Rejšek [75] at the soil texture, soil reaction, carbonates and organic carbon content levels. In addition to the incompatibility of laboratory methods, which represent a problem in pedological long-term studies [76,77], the authors concluded that the temporal changes were insignificant, and neither the leaching of carbonates nor decreases in soil reaction joined with acidification or soil environment impoverishment occurred due to nutrient depletions. Alterations in soil properties on a physicochemical basis can be expected with an uncertain trend due to the buffering capacity [78].…”
Section: Temporal Aspect Of Changes In Soil Environmentmentioning
confidence: 99%